2017
DOI: 10.1111/cge.12930
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐allelic IARS mutations in a child with intra‐uterine growth retardation, neonatal cholestasis, and mild developmental delay

Abstract: Recently, bi-allelic mutations in cytosolic isoleucyl-tRNA synthetase (IARS) have been described in three individuals with growth delay, hepatic dysfunction, and neurodevelopmental disabilities. Here we report an additional subject with this condition identified by whole-exome sequencing. Our findings support the association between this disorder and neonatal cholestasis with distinct liver pathology. Furthermore, we provide functional data on two novel missense substitutions and expand the phenotype to includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 13 publications
2
27
3
Order By: Relevance
“… 32 , 52 Autosomal-recessive IARS (encoding isoleucyl-tRNA synthetase) (MIM: 617093 ) deficiency is associated with liver disease, hypotonia, and intellectual disability. 23 , 24 In contrast to our findings with deficiency of cytoplasmic FARSB , compound heterozygous mutations in nuclear-encoded FARS2 (the mitochondrial phenylalanyl-tRNA synthetase) lead to combined oxidative phosphorylation deficiency associated with global developmental delay, refractory seizures, and lactic acidosis. 53 Interestingly, in three individuals (P1, P3, and P5) a mitochondrial disease was suspected clinically.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“… 32 , 52 Autosomal-recessive IARS (encoding isoleucyl-tRNA synthetase) (MIM: 617093 ) deficiency is associated with liver disease, hypotonia, and intellectual disability. 23 , 24 In contrast to our findings with deficiency of cytoplasmic FARSB , compound heterozygous mutations in nuclear-encoded FARS2 (the mitochondrial phenylalanyl-tRNA synthetase) lead to combined oxidative phosphorylation deficiency associated with global developmental delay, refractory seizures, and lactic acidosis. 53 Interestingly, in three individuals (P1, P3, and P5) a mitochondrial disease was suspected clinically.…”
Section: Discussioncontrasting
confidence: 99%
“… 16 Some studies also measured the amount of charged tRNA in participants’ cells or analyzed the mutated genes in yeast complementation assays. 23 , 24 , 25 , 30 , 51 However, it is unclear how well the changes observed in these assays correlate with a significant compromise of cellular translation. The puromycin incorporation assay used here is an effective way to evaluate overall protein synthesis in cultured cells, to test whether a mutation affects the cellular translational machinery and, if not, to point to a disease mechanism due to an orthogonal, non-canonical function of aaRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid line indicates dominant mode of inheritance, dashed line indicates recessive mode of inheritance. References: AARS , DARS , HARS , IARS MARS , RARS , S ARS , W ARS , ARS , QARS , GARS , KARS , AARS 2 , CARS 2 , DARS 2 , EARS 2 , FARS 2 , HARS 2 , IARS 2 , LARS 2 , MARS 2 , NARS 2 , PARS 2 , RARS 2 , S ARS 2 , TARS 2 , VARS 2 , WARS 2 , YARS 2 .…”
Section: Mitochondrial Trna Synthetases (Ars2 Genes)mentioning
confidence: 99%
“…2 Consistent with this notion, functional studies have revealed that recessive disease-associated ARS mutations cause reduced protein abundance in immunoblot assays, [5][6][7][8][9][10][11][12][13][14][15][16][17] decreased mutant enzyme activity via in vitro kinetic assays, 9,[18][19][20][21][22][23][24][25] and/or diminished ability of the mutated gene to support cellular growth in yeast complementation assays. 12,13,21,22,[26][27][28][29][30][31][32][33] As such, impaired protein translation as a consequence of decreased tRNA charging is the most likely molecular mechanism for ARS-mediated recessive disease. 2 Here, we report on four affected individuals from three unrelated families.…”
mentioning
confidence: 99%